2015
DOI: 10.1007/s00405-015-3491-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of tinnitus in patients with temporomandibular disorder: a retrospective population-based cohort study

Abstract: This study determined whether there is an increased risk of tinnitus in patients with temporomandibular joint (TMJ). We used information from health insurance claims obtained from Taiwan National Health Insurance (TNHI). Patients aged 20 years and older who were newly diagnosed with TMJ disorder served as the study cohort. The demographic factors and comorbidities that may be associated with tinnitus were also identified, including age, sex, and comorbidities of hearing loss, noise effects on the inner ear, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…The incidence of tinnitus for patients with TMD was reported by one study to be 0.82% compared to 0.3% for a control group . One study reported an incidence of 7.3%, but due to the reporting of cross‐sectional data only in this study, this was deemed to describe prevalence, and thus included in the data on prevalence below.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The incidence of tinnitus for patients with TMD was reported by one study to be 0.82% compared to 0.3% for a control group . One study reported an incidence of 7.3%, but due to the reporting of cross‐sectional data only in this study, this was deemed to describe prevalence, and thus included in the data on prevalence below.…”
Section: Resultsmentioning
confidence: 93%
“…To compare results, it is important that studies have used standardised diagnostic systems. Fourteen of the 26 included studies used the RDC/TMD while the other 12 used non‐validated questionnaires, which creates uncertainty about the TMD diagnoses . In all included studies, tinnitus is self‐reported; tinnitus can, however, also be classified using the THI .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the treatment can come in many forms, such as sound therapy, counseling, transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS) [2], temporomandibular disorder (TMD) treatment [5], acupuncture, herbal medicine, or other alternative treatments. This is why more and more data have revealed to achieve the aim, getting rid of tinnitus successfully.…”
Section: Tinnitus Treatment In Propermentioning
confidence: 99%
“…The disorders occur in over 10% of all individuals, restricting their ability to perform everyday functions at home and at work (FERENDIUK; ZAJDEL; PIHUT, 2002). TMD patients often report the presence of tinnitus as an associated symptom, and the comorbidity relationship between these changes is poorly understood (CHERIAN et al, 2013;FERNANDES et al, 2014;LEE et al, 2015). However, due to the high prevalence of such otological complaints in individuals with masticatory muscle disorders, it is speculated that there is a close relationship between tinnitus and this kind of TMD (BUERGERS et al, 2014).…”
Section: Introductionmentioning
confidence: 99%